The relationships between k-management, corporate entrepreneurship and firm's financial performance - A. Rahman, Badruddin (Faculty of Information Technology, Universiti Utara Malaysia, 2006)
In a study of Sungai Petani industrial companies, it was observed that while knowledge management offers cost savings, the real value is in more forward-looking managers that are technological entrepreneurs working in adaptive organizational environments. These managers are fundamental drivers of the technological innovation process. Their activities will create new resource combinations to make innovation possible, bringing together the technical and commercial worlds in profitable ways. Their administrative capabilities must be deployed both effectively and efficiently. Technological entrepreneurship can involve one individual (individual entrepreneurship) or the combined activities of multiple participants in an organization (corporate entrepreneurship). These companies derive benefits in faster product development, improved decision-making, more skilled employees, and enhanced services that better meet customer needs. These benefits will surface in measures such as cycletime reductions, better resource returns, higher product satisfaction indexes, and increased employee education levels. Many of the organizations surveyed now recognize that knowledge management is critical to the survival and growth of their business. They are aware of the need to distribute information throughout the organization by making use of a variety of operational knowledge management techniques. Their main concern is to connect people to the system being used for the distribution and transfer of knowledge. Knowledge management gives balance by linking the building of company's knowledge to business strategy.